Answer:
a = - 2, remainder = 21
Step-by-step explanation:
The Remainder theorem states that if f(x) is divided by (x - a) the remainder is f(a)
Since f(x) is divisible by (x - a) then remainder is zero , then
f(a) = 2a³ - 7a² + 7a² + 16 = 0 , that is
2a³ + 16 = 0 ( subtract 16 from both sides )
2a³ = - 16 ( divide both sides by 2 )
a³ = - 8 ( take the cube root of both sides )
a = [tex]\sqrt[3]{-8}[/tex] = - 2
Then
f(x) = 2x³ - 7x² - 14x + 16
Evaluate f(- [tex]\frac{1}{2}[/tex] ) for remainder on division by (2x + 1)
f(- [tex]\frac{1}{2}[/tex] ) = 2(- [tex]\frac{1}{2}[/tex] )³ - 7(- [tex]\frac{1}{2}[/tex] )² - 14(- [tex]\frac{1}{2}[/tex] ) + 16
= 2(- [tex]\frac{1}{8}[/tex] ) - 7([tex]\frac{1}{4}[/tex] ) + 7 + 16
= - [tex]\frac{1}{4}[/tex] - [tex]\frac{7}{4}[/tex] + 23
= - [tex]\frac{8}{4}[/tex] + 23
= - 2 + 23
= 21